The Peopling of the Pampas and Patagonia - Miotti, Laura Lucia
Consider South America, a continent so vast it could swallow the United States twice over. Even today, only natives have ever set foot on some inner reaches. Indeed, Native Americans have colonized every clime and exploited every ecological niche in a process that began when Northeast Asians crossed the Bering Land Bridge and, after a layover of some thousands of years, set out on foot or in watercraft in search for greener pastures to the south. These bold explorers share the same genetic lineage as other Native Americans who colonized North America (MT 34- 2, “Beringian Child’s genome reveals the founding population of the First Americans”). Now, more than 10,000 years later, Laura Miotti has set for herself and her colleagues a staggering task: To determine how South America was colonized. Fil: Miotti, Laura Lucia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Arqueología; Argentina